Assessing the role of riverbank erosion in reservoir siltation using remote sensing: Case of the Ibn Battouta Dam - Imane Zada; Mohamed Chikhaoui; Mustapha Naimi; Oumayma Bassairate; Lacina Coulibaly (Universitas Sebelas Maret, 2026)
In Morocco, research on dam siltation has largely concentrated on upstream watershed erosion, often disregarding reservoir bank erosion. This study aimed to bridge this gap by analyzing the morphological evolution of the banks of the Ibn Battouta Dam, located in the western Rif region, over a 40-year period. Remote sensing and GIS data were used to achieve this goal. Two sets of satellite images were analyzed: Landsat images (1984-2014) and high-resolution Sentinel-2A images (2015-2024). The Normalized Difference Water Index (NDWI) has been applied to extract water surfaces and analyze the shoreline changes. A reference digital elevation model (DEM) was constructed to represent the topography prior to dam construction, enabling a comparison between the theoretical and observed reservoir contours. Bathymetric data collected in 2013 and 2020 were incorporated to enhance the precision of our analysis. The results highlight significant modifications along the banks, primarily caused by erosion and sediment accumulation, with influencing factors including tributary inflows, soil composition, and prevailing winds. Morphological changes were quantified using the S-segment method based on the elevation difference (Δh) and slope angle (α) along the maximum gradient. The findings confirm progressive bank degradation, emphasizing the need to include bank erosion processes in dam siltation assessments.